Effects of f(R) Model on Dynamics of Axial Shear-Free Dissipative Fluids. (1st April 2016) - Sharif, M.; Nasir, Zunaira
Abstract: We present a general analysis on non-static axial system with dissipative shear-free anisotropic fluid using polynomial inflationary f(R) model. We study the effects of dissipation on the dynamics of geodesic matter distribution. This leads the system either to rotation-free or expansion-free but not both simultaneously under geodesic condition. It is found that the system preserves its symmetry in both cases. For the rotation-free case, when there is no dissipation and Ricci scalar is constant, the axial system reduces to FRW universe model. This is exactly the same result obtained in general relativity.